Effects of Yishenjiangzhuo granules on immunity and bone metabolism in patients with stage 3-4 chronic kidney disease - Zheng, Jing; Lin, Yingda; Huang, Lu; Chen, Caifeng; Zheng, Xuemin; Wu, Xinhong; Liu, Ciyun (Journal of traditional Chinese medicine, 2013)
To determine the effects of Yishenjiangzhuo granules (YJG) on bone metabolism and to explore the changes in levels of bone Gla protein (BGP), tartrate-resistant acid phosphatase (TRAP), as well as their relationships with levels of B cells, regulatory T cells (Treg) and interleukin (IL)-17 in patients with stage 3-4 chronic kidney disease (CKD) before and after treatment. Fifty-three stage 3-4 CKD patients were divided randomly into two groups: YJG treatment and control. Peripheral blood was taken from two groups of CKD patients and 21 healthy subjects in the normal group. The parameters determined were the levels of CD4+, CD19+, CD19+ CD69+, CD19+ av, Treg (CD4 + CD25 + CD127lo), BGP, TRAP, IL-17, calcium, phosphate, blood urea nitrogen, serum creatinine (SCr), hemoglobin (Hb) in peripheral blood, and urinary creatinine. Calcium-phosphate products and endogenous creatinine clearance rate (CCr) were calculated according to standard protocols. In YJG and control groups, SCr levels were lowered (P < 0.01) after treatment, whereas CCr (P < 0.05) as well as Hb and albumin levels (P < 0.01) were increased. The changes in levels of CCr and SCr in the YJG group were more significant. After treatment, CD19+CD69+ and Treg levels in the two groups varied (P < 0.01) compared with those of the normal group; the level of CD19+ increased but the levels of CD4+ and CD19 + AV decreased (P < 0.01) in both groups. Compared with the control group, the changes of CD19+ and CD19 + AV in the YJG group were more apparent (P < 0.05). Compared with the normal group, levels of IL-17 in both groups increased significantly (P < 0.01), and the difference in the control group was more significant (P < 0.05). After treatment, the TRAP level increased (P < 0.05), but the difference in BGP level (P > 0.05) was not significant. In stage 3-4 CKD patients, B cells and IL-17 participated in the induction of osteoclast activation. YJG could also elevate the level of B cells and decrease their apoptosis, but showed no significant effects on active B cells, IL-17 or osteoclast activity.